Service discovery in ubiquitous computing: a first step towards sensor-based context identification - Pertselakis, Minas; Tsapatsoulis, Nicolas (My University, 2003)
In this paper we propose an architecture for modeling the service discovery process of computing devices operating in ubiquitous computing environments. Forming wireless ad-hoc networks requires service discovery protocols that support both proximity based detection and abstract level service matching. In the proposed architecture, primitive services, provided by sensors and actuators, are indirectly located through polling while composite service matching is based on the intelligent agent philosophy. In this way, the proposed service discovery approach, exploits the spread of proximity based device detection and the dynamics and openess of the agent platforms
Keywords: Ubiquitous computing environments; Wireless ad-hoc networks